Discovery of TRAF-2 and NCK-interacting kinase (TNIK) inhibitors by ligand-based virtual screening methods1. Issue 8 (5th August 2015) - Bujak, Anna; Stefaniak, Filip; Zdzalik, Daria; Grygielewicz, Paulina; Dymek, Barbara; Zagozda, Marcin; Gunerka, Pawel; Lamparska-Przybysz, Monika; Dubiel, Krzysztof; Wieczorek, Maciej; Dzwonek, Karolina
<x xml:space="preserve">Abstract</x> TRAF-2 and NCK-interacting kinase (TNIK) is a serine–threonine kinase with a proposed role in Wnt/β-catenin and JNK pathways.